2007
DOI: 10.1109/tmag.2006.888402
|View full text |Cite
|
Sign up to set email alerts
|

Design, Fabrication, and Control of Components in MEMS-Based Optical Pickups

Abstract: Small-form-factor optical pickups and disk drives have been an area of intense research since the rise of portable consumer electronic products. In current technology, most of the devices are manufactured by the precision assembly of discrete miniaturized optomechanical components. The assembly process can be simplified and cost reduced by using the batch fabrication processes developed in microelectromechanical systems (MEMS). In this paper, the fabrication and testing of optical and actuator components for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
(19 reference statements)
1
8
0
Order By: Relevance
“…This is widely used to evaluate a decapod crustacean's health status under different treatments of probiotics, immunostimulants and environmental stress. Most studies showed that animals with better phagocytic activity have better disease resistance [67,68]. In the present study, the phagocytic activity of experimental groups of shrimp was significantly (P < 0.05) increased than control group after challenge experiment.…”
Section: Concentration Of Fucoidan (%)supporting
confidence: 52%
“…This is widely used to evaluate a decapod crustacean's health status under different treatments of probiotics, immunostimulants and environmental stress. Most studies showed that animals with better phagocytic activity have better disease resistance [67,68]. In the present study, the phagocytic activity of experimental groups of shrimp was significantly (P < 0.05) increased than control group after challenge experiment.…”
Section: Concentration Of Fucoidan (%)supporting
confidence: 52%
“…If someone tells you about a medication that will quickly cure your cold or a website for last-minute travel deals, it demonstrates the sharer's knowledge and expertise. Consistent with this perspective, more useful news stories (4, 6) and marketing messages (21) are more likely to be widely shared.…”
Section: Content Effects: How Do Content Characteristics Affect Sharing?mentioning
confidence: 83%
“…Movies, news, emails, and social anecdotes are all more likely to be shared if they are higher in emotional intensity (4,21,28,29). Along these lines, more emotional scientific discoveries, or scientific discoveries that are framed in a more emotional manner, should be more likely to be shared.…”
Section: Content Effects: How Do Content Characteristics Affect Sharing?mentioning
confidence: 99%
“…Shih et al also proposed a system assembly method for precisely aligning components by using virtual images of the photodetector (PD) and laser from the HOE diffraction. Based on the design configuration, there have been a series of studies presented to fulfill and strengthen its feasibility, such as the micro blue-light objective lens with the numerical aperture (NA) of 0.65 [12], the dual-stage seesaw-swivel actuator [13][14][15][16], the astigmatic reflector [17], and the fabrication using microelectromechanical systems (MEMS) technologies [18,19]. The servo characteristics of the design have been successfully verified by Hou et al [20][21][22] for the red-light system and by Lin et al [23] for the blue-light system, respectively.…”
Section: Introductionmentioning
confidence: 99%